2020
DOI: 10.1016/j.jagp.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Nonpharmacological Treatment of Apathy in Brain Disorders

Abstract: Highlights  The present paper aimed at collecting recommendations on non-pharmacological treatment (NPT) for apathy and on the role of new Information and Communication Technologies (ICT) in this domain.  Based on the experts' opinion, NPT should be tailored to deficits, clinical objectives, and preferences of each patient. ICT may help to improve treatment personalization, increase motivation, and aid remote treatment delivery.  Further structured research is needed to determine NTP efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…For example, in addition to other mood and behavioral treatments (i.e., contingency management), improving motivation and self-direction and may serve as an additional buffer to enhance the likelihood of successful METH substance use treatment and relapse prevention through improving abstinence self-efficacy. Indeed, abstinence self-efficacy is an important predictor of these outcomes ( Tuliao & Liwag, 2011 ), and there is promising work emerging regarding the treatment of apathy by pharmacological and non-pharmacological means ( Manera, 2019 , Roth et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in addition to other mood and behavioral treatments (i.e., contingency management), improving motivation and self-direction and may serve as an additional buffer to enhance the likelihood of successful METH substance use treatment and relapse prevention through improving abstinence self-efficacy. Indeed, abstinence self-efficacy is an important predictor of these outcomes ( Tuliao & Liwag, 2011 ), and there is promising work emerging regarding the treatment of apathy by pharmacological and non-pharmacological means ( Manera, 2019 , Roth et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current treatment programs addressing comorbid substance use disorder and depression with techniques such as behavioral activation ( Daughters, 2016 ) may be more efficacious if apathy was also an integrated treatment focus, particularly in METH. Though there is not yet a gold standard for apathy treatment, potential pharmacological and psychological treatments (e.g., acetylcholinesterase inhibitors, dopamine-reuptake inhibitors, and cognitive-communication therapies) are being investigated ( Manera, 2019 , Roth et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apathy is a common neuropsychiatric syndrome observed across many neurocognitive and psychiatric disorders. In the study of Valeria et al [ 87 ], 20 experts reported that information and communications technology is “very appropriate” for apathy nonpharmacological treatment. Among all the studies included in this review, none of the studies using measurement tools detected changes in apathy before and after the intervention; however, we found some benefits in terms of motivation and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…39 Because of the lack of an established pharmacological treatment of apathy in DAT, nonpharmacological therapies, such as the use of information and communication technologies or occupational therapy, are still first-line recommendations. 40…”
Section: Discussionmentioning
confidence: 99%